Linguistic (in)visibility in Islamabad’s landscape: A nexus analysis of policies, practices and perceptions - Turab Hussain; Muhammad Haseeb Nasir; Aziz Ullah Khan (Russian Journal of Linguistics, 2025)
The linguistic landscape (LL) in multilingual communities often reflects the complex relationship of language policies, practices, and people’s perceptions of these policies and practices. This complex policy-practice-perception nexus leads to questions of linguistic inclusivity in contexts such as Pakistan. This study, therefore, attempted to find the nexus of spatial practices, language policies, and residents’ perceptions of language use in the LL of Islamabad. To improve the structure of the highlighted sentence, it may be rewritten as: Data included a sample of 1213 pictures collected from Islamabad; text from the Pakistani constitution, parliamentary debates, and political talk shows; and three focus group discussions with the local residents. A nexus analysis of the data (Hult 2018) was carried out to see the extent of correspondence among the three data sets. The findings revealed that English, Urdu, and Arabic remain the most visible languages (respectively) in the LL of Islamabad, and the indigenous languages lack visibility. The macro-level language policies were also found to promote the three languages, deeming them necessary for the constitutional and ideological makeup of Pakistan. The residents, too, tended to favour the use of these languages in the LL of Islamabad, despite their demonstration of affection for their native languages. The findings of the study have serious implications for the Pakistani indigenous languages, and indicate a need for inclusive language policies and awareness initiatives to protect linguistic diversity in Pakistan.